Personal Guarantee Responsibility for Debtors Who Default on Banking Credit - Syahid, Annisa Fitri Nur; Yunanto, Yunanto (Jurnal Daulat Hukum, 2023)
The aim of this research is to understand the concept of personal guarantee and the process of resolving personal guarantees for debtors who are in default. This research uses normative methodsnamely doctrinal legal research or commonly referred to as library-based legal research which focuses on studying primary and secondary legal materials. The result obtained is that in the context of a credit agreement, personal guarantee responsibility is the obligation of a third party, called the guarantor, to guarantee credit payments if the main party borrowing the money (the debtor) experiences default, that is, fails to fulfill its obligations in accordance with the credit agreement. Personal guarantee responsibility is a form of protection given to banks or financial institutions that provide credit by securing credit payments through personal guarantees. In a situation of default by the debtor, the guarantor becomes the party responsible for paying off outstanding credit obligations.